2012
DOI: 10.1124/dmd.112.049635
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Inhibitory Effect of Apple and Orange Juices, but Not Grapefruit Juice, on OATP2B1-Mediated Drug Absorption

Abstract: Enzyme-based grapefruit juice (GFJ)-drug interactions are mainly due to mechanism-based irreversible inhibition of metabolizing enzyme CYP3A4 by GFJ components, but the transporter organic anion transporting polypeptide (OATP)2B1 is also a putative site of interaction between drugs and fruit juices (FJ) in the absorption process. Here we aimed to investigate the effect of preincubation with FJ on OATP2B1-mediated transport of drugs in vitro. When OATP2B1-expressing Xenopus oocytes were preincubated with GFJ, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 33 publications
(51 reference statements)
1
39
0
2
Order By: Relevance
“…Here, before initiation of uptake reaction, SN-38 was dissolved in 50 mM K 2 HPO 4 buffer (pH 9.0) or KH 2 PO 4 buffer (pH 3.0) overnight to prepare carboxylate or lactone form of SN-38, respectively. Our laboratory has reported that a long-lasting inhibition of OATP2B1 was observed when cells were preincubated with apple juice (Shirasaka et al, 2013); however, the assessment of long-lasting inhibition of uptake of SN-38 was beyond the scope of the current work. Accordingly, for the inhibition studies, inhibitors were included only during uptake reaction.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Here, before initiation of uptake reaction, SN-38 was dissolved in 50 mM K 2 HPO 4 buffer (pH 9.0) or KH 2 PO 4 buffer (pH 3.0) overnight to prepare carboxylate or lactone form of SN-38, respectively. Our laboratory has reported that a long-lasting inhibition of OATP2B1 was observed when cells were preincubated with apple juice (Shirasaka et al, 2013); however, the assessment of long-lasting inhibition of uptake of SN-38 was beyond the scope of the current work. Accordingly, for the inhibition studies, inhibitors were included only during uptake reaction.…”
Section: Methodsmentioning
confidence: 87%
“…It was reported that the plasma concentration of fexofenadine after oral administration was decreased by coingestion with fruit juices, presumably owing to inhibition of intestinal uptake (Dresser et al, 2002). We suggested a significant contribution of OATP2B1 to intestinal absorption of fexofenadine and proposed that this transporter is a site of interaction with fruit juice components (Imanaga et al, 2011;Shirasaka et al, 2013Shirasaka et al, , 2014. OATP1B1 and 1B3 have broad substrate selectivity and mediate hepatic uptake of various drugs (Shitara et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Inhibition of OATP2B1-mediated drug absorption in the intestine and drug uptake into the liver could lead to clinically relevant drug-drug and drug-food interactions. It was reported that grapefruit and orange juices significantly inhibited OATP2B1-mediated uptake of E3S and glibenclamide (Satoh et al, 2005;Shirasaka et al, 2013a) while apple and orange juices induced a remarkable decrease in OATP2B1-mediated fexofenadine uptake (Imanaga et al, 2011;Shirasaka et al, 2013b), indicating that citrus juices might inhibit the intestinal absorption of anionic drugs. In vivo studies showed that grapefruit, orange, and apple juices greatly reduced the plasma concentration of aliskiren, probably by inhibiting its OATP2B1-mediated influx in the small intestine (Tapaninen et al, 2010(Tapaninen et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…21) Our results indicate that the inhibitory effect of grapefruit juice on OATP dissipates faster than its effect on CYP3A4 activity, which is sustained for at least 48 h. Very recently, Shirasaka et al reported the effects of pre-incubation with fruit juices on OATP2B1-mediated transport of specific substrates in vitro. 22) Their results indicated that OATP2B1 is functionally impaired through both competitive and long-lasting inhibition mechanisms by apple juice and orange juice, but not by grapefruit juice. Our results from a clinical investigation are in agreement with these in vitro findings.…”
Section: Discussionmentioning
confidence: 99%